Biodiversity and characterization of high lipid content microalgae in Porong River Estuary East Java, Indonesia - SRI NURHATIKA; DINI ERMAVITALINI; TRIONO BAGUS SAPUTRO; YUDI APRIYATMOKO (Biodiversitas Journal of Biological Diversity, 2018)
Nurhatika S, Ermavitalini D, Saputro TB, Apriyatmoko Y. 2018. Biodiversity and characterization of high lipid content microalgae in Porong River Estuary East Java, Indonesia. Biodiversitas 19: 627-632. Microalgae are aquatic unicellular or multicellular microscopic photoautotroph organisms. High lipid content in microalgae biomass can be used as raw material for biodiesel. Porong river estuary is one of the sites of industrial waste disposal. The polluted waters considered will affect the lipid microalgae metabolism. The main research aims are to isolate and characterize of high lipid content microalgae found in Porong river estuary through the selection of qualitative lipid content. Sampling was conducted at three different stations. Isolation was conducted in solid agar media enriched with Porong River Estuary sterile water and using streak plate method. The isolated microalgae were characterized using a light microscope and to be matched with identification books. The lipid content was determined qualitatively by coloring the isolated-microalgae cells with Nile Red, an intracellular lipid dye then observed its luminescence color under a fluorescence microscope. Several genera of microalgae that can be isolated in this study are Oscillatoria, Nitzschia, Merismopedia, Navicula, Nannochloropsis, and Melosira. The results of qualitative lipid analysis show that the genus Nannochloropsis and Nitzschia have high intracellular lipid accumulation.